2006
DOI: 10.1007/s00134-006-0329-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Binax NOW Streptococcus pneumoniae urinary antigen assay in intensive care patients hospitalized for pneumonia

Abstract: This first clinical evaluation of ICT in intensive care patients hospitalized for suspicion of community-acquired pneumonia, demonstrated performance in accordance with published data even in the case of prior antibiotics. Its clinical interest and impact on antibiotics policy remain to be refined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…The proportion with severe disease, as indicated by pneumonia severity index (PSI) class IV or V, ranged from 23 to 61%. One study reported on a cohort of patients admitted to an intensive care unit (ICU) (36). Prior use of antibi- Excluded a Designations: blood ϩ , positive blood culture; sputum ϩ , positive Gram stain and/or sputum culture; pleural fluid ϩ , positive culture from pleural fluid; nasopharynx ϩ , positive culture from the nasopharynx; BAL ϩ , positive culture from bronchioalveolar lavage fluid; respiratory ϩ , positive culture from any respiratory sample; TBAS ϩ , tracheobronchial aspiration; BinaxNOW-SP ϩ , positive urinary BinaxNOW-SP test (to be included in the meta-analysis, studies had to report sufficient detail to separate these results into true and false positives).…”
Section: Search Results and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion with severe disease, as indicated by pneumonia severity index (PSI) class IV or V, ranged from 23 to 61%. One study reported on a cohort of patients admitted to an intensive care unit (ICU) (36). Prior use of antibi- Excluded a Designations: blood ϩ , positive blood culture; sputum ϩ , positive Gram stain and/or sputum culture; pleural fluid ϩ , positive culture from pleural fluid; nasopharynx ϩ , positive culture from the nasopharynx; BAL ϩ , positive culture from bronchioalveolar lavage fluid; respiratory ϩ , positive culture from any respiratory sample; TBAS ϩ , tracheobronchial aspiration; BinaxNOW-SP ϩ , positive urinary BinaxNOW-SP test (to be included in the meta-analysis, studies had to report sufficient detail to separate these results into true and false positives).…”
Section: Search Results and Patient Characteristicsmentioning
confidence: 99%
“…In the absence of an effect of antibiotics with the BinaxNOW-SP test, this would artificially increase the rate of discordant results for BinaxNOW-SP-positive and culture-negative samples. The effect of prior antibiotic treatment on the sensitivity of the BinaxNOW assay is unclear, with some studies reporting decreased sensitivity (4, 36, 39, 41) while others did not (4,36,40,50).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this technique does not depend on treatment with antibiotics (Andreo et al, 2006;Lasocki et al, 2006) and it has demonstrated to be accurate for direct urine and CSF testing. However, it has a low sensitivity (the manufacturer specifies a detection limit of about 10 5 cfu mL −1 in CSF (Gisselsson-Solén et al, 2007), a poor selectivity towards other streptococci (Streptococcus mitis, Streptococcus oralis and other ␣-hemolytic streptococci), and various pathogenic bacteria (Staphylococcus aureus and H. influenzae) including Escherichia coli (Navarro et al, 2004;Moore et al, 2004;Lasocki et al, 2006;Gisselsson-Solén et al, 2007). Furthermore, this test fails to distinguish infants and children (which are more likely to be asymptomatic carriers of pneumococci than adults) with pneumococcal pneumonia from those who are merely colonized (Dowell et al, 2001;Samra et al, 2003;Navarro et al, 2004;Andreo et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…This test is commercially available, rapid ( ∼ =15 min), easy-to-use and was approved by the US Food and Drug Administration (FDA) for use in the United States (Dowell et al, 2001;Samra et al, 2003). The efficiency of this technique does not depend on treatment with antibiotics (Andreo et al, 2006;Lasocki et al, 2006) and it has demonstrated to be accurate for direct urine and CSF testing. However, it has a low sensitivity (the manufacturer specifies a detection limit of about 10 5 cfu mL −1 in CSF (Gisselsson-Solén et al, 2007), a poor selectivity towards other streptococci (Streptococcus mitis, Streptococcus oralis and other ␣-hemolytic streptococci), and various pathogenic bacteria (Staphylococcus aureus and H. influenzae) including Escherichia coli (Navarro et al, 2004;Moore et al, 2004;Lasocki et al, 2006;Gisselsson-Solén et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…La sensibilité de l'antigénurie pneumocoque (immunochromatographie) varie de 52 à 88 % dans les pneumopathies et de 65 à 92 % chez des patients bactériémiques [59][60][61], avec une spécificité de 90 à 100 %. Chez des patients de réanimation, la sensibilité, la spécificité et les valeurs prédictives positives et négatives étaient de 72, 90, 68 et 92 % respectivement [62]. Chez les enfants, en raison du taux de portage élevé de pneumocoque, la spécificité est mauvaise (faux-positifs variant de 10 à 50 %) [61,63,64].…”
Section: Méthodologieunclassified